Inventing ritual: moving images of social reality in contemporary art - Vogt, N (2017)
Ritual is a notion that the art world has increasingly reclaimed. From critical writing that zealously identifies rituals to artists who qualify their work as ritualistic, the notion circulates, poking at the boundaries of art practice. The pattern raises critical questions for art history: does it vanish the distinction between art and social practices, casting art’s separation from ritual as a passing historical phase? What are the distinctions in the first place between representing and producing a ritual? These concerns come to the fore with moving images, given that ritual has long been at the heart of ethnographic film, while the very act of filming is becoming central to a growing number of social customs. Addressing these relationships, this thesis focuses on video work since the late 1990s. The thematic research moves through three case studies: series of works by Mike Kelley, Pierre Huyghe, Ryan Trecartin and Lizzie Fitch, while keeping a comparative view towards other observers and producers of ritual in premodern painting, ethnographic filmmaking, post-internet practices, mainstream cinema, and homemade videos. Among the most influential artists at the turn of this century, Kelley, Huyghe, Trecartin and Fitch share the singular practice of restaging, for and through film, the rituals that surround them, from high school hazing and carnivals to coronations, corporate team-building, Halloween, Valentine and May Days, suburban street fairs, birthdays, and the new observances of social media. Through close study of the artworks and of moving image tropes that shape social imaginaries, the thesis suggests that these artists produce new insights into contemporary human behaviour. While art and ritual tend to be tackled as coded objects to be deciphered, holding condensed information about the societies to which they point, anthropological theory that considers ritual for what it does (rather than what it symbolises) invites us to examine them instead as practices where portions of social reality are produced – formalised and reinvented.